1, 3, 5, 9-Tetra(4-(1, 2, 2-triphenylvinyl)phenyl)pyrene (TTPE(1, 3, 5, 9)Py): a prominent blue AIEgen for highly efficient nondoped pure-blue OLEDs. Issue 48 (25th November 2020) - Xie, Fuli; Ran, Huijuan; Duan, Xuewei; Han, Ruijun; Sun, Huaming; Hu, Jian-Yong
Abstract : By integrating four tetraphenylethylene (TPE) groups into the pyrene ring at 1, 3, 5, 9-positions, a highly twisted pyrene-based blue AIEgen has been developed for highly efficient nondoped pure-blue OLEDs. Abstract : Great efforts are being continuously devoted to develop efficient pure blue emitters with a small efficiency roll-off and realize full-color displays. Here, by attaching a representative AIE unit tetraphenylethylene (TPE) to the 1-, 3-, 5- and 9-positions of the pyrene ring, a new highly twisted pyrene-based blue AIEgen, 1, 3, 5, 9-tetra(4-(1, 2, 2-triphenylvinyl)phenyl)pyrene (TTPE(1, 3, 5, 9)Py ), was designed and synthesized. The new blue AIEgen has good thermal and morphological stability and exhibits remarkable enhanced photoluminescence (PL) in the solid state. The aforementioned characteristics and appropriate energy levels ensured that TTPE(1, 3, 5, 9)Py could act as a prominent blue emitter in an OLED. The TTPE(1, 3, 5, 9)Py -based nondoped device displayed a pure-blue emission ( λ EL : 468 nm) and a low turn-on voltage ( V on : 3.2 V) with a maximum EQE, current efficiency (CE) and luminance of 4.10%, 7.38 cd A −1 and 11 849 cd m −2, respectively. More importantly, the TTPE(1, 3, 5, 9)Py -based device showed a negligible efficiency roll-off and good color purity. This excellent performance of the nondoped blue OLED is attributed to the ingenious molecular design, and this work will provide a novel approach for constructing valuable blue emitters based on pyrene.